Fundamentals of Materials science and engineering : An Intergrated approach - Callister, William D. (John Wiley & Sons Singapore Pte. Ltd, 2016)
Fundamentals of Materials Science and Engineering: An Integrated Approach, 5th Edition SI Version takes an integrated approach to the sequence of topics one specific structure, characteristic, or property type is covered in turn for all three basic material types: metals, ceramics, and polymeric materials. This presentation permits the early introduction of non-metals and supports the engineer's role in choosing materials based upon their characteristics. Using clear, concise terminology that is familiar to students, Fundamentals presents material at an appropriate level for both student comprehension and instructors who may not have a materials background.